The Influence of Anxiety Levels Facing Medical Exams to Urinary Incontinence in YARSI University Medical Students Class of 2019 and 2020, and A Review Through Islamic Perspectives - Muhammad Achmad Yani; Nunung Ainur Rahmah; Citra Fitri Agustina; Firman Arifandi (Junior Medical Journal, 2023)
Background: Urinary incontinence is the involuntary excretion of urine at any given condition. Medical exams experienced by medical students could induce anxiety, which could lead to urinary incontinence. Through an Islamic viewpoint, individuals suffering from urinary incontinence are constantly unclean and require certain ways to practice worship. This study aims to determine the relationship between anxiety levels and age; anxiety levels and gender; the correlation between anxiety levels and urinary incontinence; identifying anxiety levels; and the severity of urinary incontinence symptoms within YARSI University Medical Students Class of 2019 and 2020, as well as how to pray and ablute for individuals with urinary incontinence.Method: This study is qualitative research done as an analytical observational study with cross-sectional study design. The research instrument used the Urogenital Distress Inventory questionnaire (UDI-6) and the Hamilton Anxiety Rating Scale (HARS). The research was conducted on YARSI University Medical Students Class of 2019 and 2020 with a sample size of 209 participants. Data analysis utilized Kruskal Wallis, Kolmogorov-Smirnov, and Spearman Correlation statistical tests.Results: The level of anxiety experienced by most students is a mild level of anxiety. The highest severity of urinary incontinence symptoms was experienced by students with moderate to severe anxiety levels. No significant relationship was found between age and gender with anxiety levels. There is a positive correlation with moderate strength between the level of anxiety and urinary incontinence.Conclusion: No relationship was found between anxiety levels facing medical exams with age nor gender and a positive correlation with moderate strength was found between anxiety levels medical exams and urinary incontinence within YARSI University Medical Students Class of 2019 and 2020.